Mechanisms of microbial infection and wound healing in diabetic foot ulcer: pathogenicity in the inflammatory-proliferative phase, chronicity, and treatment strategies - Wang, Qi; Liu, Chuyu; An, Jing; Liu, Jing; Wang, Yongpeng; Cai, Yulan (Frontiers in Endocrinology, 2025)
Diabetes has long been recognized as a significant global public health burden, with its complications posing serious threats to patient health and survival. Diabetic foot ulcer (DFU) is a common and severe complication of diabetes, and its prognosis is closely associated with diabetic foot infection. Diabetic foot infections (DFI) can lead to chronic, non-healing wounds and, in severe cases, may necessitate amputation. Microbial infection, the primary form of diabetic foot infections, disrupts the inflammatory and proliferative phases of DFU wound healing by forming biofilms and expressing virulence factors, ultimately contributing to the chronicity of DFU. Despite extensive research on DFU treatment, effective management remains a significant challenge due to its high susceptibility to microbial infection and frequent recurrence. This review integrates microbial infections with the physiological processes of wound healing to systematically elucidate the major pathogenic microorganisms associated with diabetic foot infections and their key pathogenic mechanisms in the healing process. In addition, we summarize current strategies for both systematic and individualized management of DFU. From etiology and pathological mechanisms to clinical treatment, this review provides new insights into the pathological mechanisms underlying chronic DFU and offers valuable guidance for clinical practice and scientific research.